2014
DOI: 10.1007/s00167-014-3438-y
|View full text |Cite
|
Sign up to set email alerts
|

Autograft soaking in vancomycin reduces the risk of infection after anterior cruciate ligament reconstruction

Abstract: Case control study, retrospective comparative study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 26 publications
9
102
0
1
Order By: Relevance
“…1 The top five journals which published the most studies and reports related to anterior cruciate ligament reconstruction. complications include OA after ACL reconstruction, 26 meniscal tears at the moment of trauma or during surgery and together with OA, 27 septic arthritis following ACL reconstruction, 28 and nerve injuries. 29 The knee is also one of the most common sites of injury in skeletally immature athletes.…”
Section: Discussionmentioning
confidence: 99%
“…1 The top five journals which published the most studies and reports related to anterior cruciate ligament reconstruction. complications include OA after ACL reconstruction, 26 meniscal tears at the moment of trauma or during surgery and together with OA, 27 septic arthritis following ACL reconstruction, 28 and nerve injuries. 29 The knee is also one of the most common sites of injury in skeletally immature athletes.…”
Section: Discussionmentioning
confidence: 99%
“…One is graft soaking in vancomycin, which has been demonstrated to be effective. 16,17 Despite this, antibiotic treatment guidelines remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to new prophylactic measures described to decrease infection rate following ACLR, recent investigations demonstrated that presoaking the autograft in a diluted solution of vancomycin is effective for this purpose [24][25][26]. Other measures, such as the use of gentamicin irrigation solution, have been shown as less effective [27].…”
Section: Aetiopathologymentioning
confidence: 97%